Perlindungan Masyarakat Hukum Adat di Wilayah Pesisir Pasca Berlakunya UU Nomor 11 Tahun 2020 Tentang Cipta Kerja - Mohammad Zamroni; Rachman Maulana Kafrawi (Perspektif Hukum, 2021)
Indonesia as an archipelagic country consisting of large and small islands separated by the ocean with geographical conditions has a total area of ​​7,827,087 Km2 and is located in Equatorial emeralds have a wealth of abundant natural resources, especially in the sea ​​and coastal areas which cover of the territory of Indonesia (5.8 million Km2). Article 18 B paragraph (2) and Article 28 I paragraph (3) of the 1945 Constitution of the Republic of Indonesia as the constitutional basis for recognition and protection the rights of indigenous peoples in coastal areas and small islands. Resource wealth nature in the form of coastal areas and small islands controlled and managed by the state tothe greatest prosperity of the people. State recognition of the existence of the legal community customs related to natural resources are inconsistent. The formulation of the problem from this research is (1) The legal construction of the Job Creation Law on the protection of customary law communities in the territory coast. (2) Implications of the Job Creation Law on the protection of customary law communities in the region coast. The research method in this writing is normative juridical. In summary, the result of In this research, the desired law is a law that provides protection against community members including customary law communities in coastal areas and islands small island, then an impartial legal instrument in the recognition of existence Indigenous Law Communities, for example in the Job Creation Law, which has not been in favor of Protection of Indigenous Peoples in Coastal Areas and Small Islands.